2022
DOI: 10.3389/fmicb.2022.935919
|View full text |Cite
|
Sign up to set email alerts
|

Circadian dysregulation induces alterations of visceral sensitivity and the gut microbiota in Light/Dark phase shift mice

Abstract: BackgroundIt is well-established that several features of modern lifestyles, such as shift work, jet lag, and using electronics at night, disturb normal circadian rhythm and increase the risk of suffering from functional gastrointestinal disease. Although substantial evidence demonstrates that shift work is closely correlated with the symptoms of visceral hypersensitivity, few basic studies have revealed the mechanism of visceral hypersensitivity induced by circadian rhythm disturbance, especially light/dark p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Circadian rhythm disruption can also lead to the loss of rhythmicity in intestinal Lactobacillus and circulating tryptophan metabolites, contributing to inflammatory diseases and dysregulation of gut integrity 102 . Another study demonstrated that circadian rhythm disturbance induced by LD cycle shifts could trigger visceral hypersensitivity resembling the pathophysiology of irritable bowel syndrome, mediated by GM alterations such as Firmicutes and Proteobacteria, as well as their metabolites like tryptophan and steroid hormones 103 . It is well‐known that circadian rhythms control the GM and its key metabolic outputs, including tryptophan metabolites, which collectively contribute to the maintenance of host immunity 104 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circadian rhythm disruption can also lead to the loss of rhythmicity in intestinal Lactobacillus and circulating tryptophan metabolites, contributing to inflammatory diseases and dysregulation of gut integrity 102 . Another study demonstrated that circadian rhythm disturbance induced by LD cycle shifts could trigger visceral hypersensitivity resembling the pathophysiology of irritable bowel syndrome, mediated by GM alterations such as Firmicutes and Proteobacteria, as well as their metabolites like tryptophan and steroid hormones 103 . It is well‐known that circadian rhythms control the GM and its key metabolic outputs, including tryptophan metabolites, which collectively contribute to the maintenance of host immunity 104 .…”
Section: Discussionmentioning
confidence: 99%
“…102 Another study demonstrated that circadian rhythm disturbance induced by LD cycle shifts could trigger visceral hypersensitivity resembling the pathophysiology of irritable bowel syndrome, mediated by GM alterations such as Firmicutes and Proteobacteria, as well as their metabolites like tryptophan and steroid hormones. 103 It is well-known that circadian rhythms control the GM and its key metabolic outputs, including tryptophan metabolites, which collectively contribute to the maintenance of host immunity. 104 Our work further expanded upon the understanding of the intricate relationship between circadian rhythms and the GMliver-brain axis in response to different LD cycles.…”
Section: The Homeostatic Crosstalk In Gm-liver-brain Axis In Response...mentioning
confidence: 99%
“…48 Currently, as it is possible to provide full-spectrum microbiota, FMT is thought to be an effective microbial therapy for diseases and a valid technique to evaluate the contribution of microbiota in attenuating diseases. 49 For example, FMT was performed to confirm the relationship between the light/dark phase shift, gut microbiota, and visceral hypersensitivity, 50 or to investigate the ame-liorating effect of phloretin on colitis through regulating microbiota. 51 FMT was also used to explore the mechanism between gut microbial dysbiosis and the pathogenesis of PD.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Disruption in circadian rhythm also may increase progression of already existing cancer. Rats with sarcoma have increased tumor growth when kept in the alternative light/dark cycle compared to the constant cycle [23]. A study by Bollati et al where they examined peripheral blood from male shift workers showed night shift potentially has induced DNA methylation defect including changes in Alu repetitive elements methylation and gene-specific methylation of inflammatory genes such as IFN-γ and TNF-α [24].…”
Section: Review Disruption Of Circadian Rhythm and Role Of Melatonin ...mentioning
confidence: 99%
“…With increasing evidence of night-shift workers and their cancer risk, it is imperative to conduct this type of experiment. Since there is evidence in animals that artificial lights at night can increase cancer risk [2,23], it might be imperative to conduct studies examining artificial light at night with cancer risk in night-shift workers and if implementing devices such as blue lightblocking glasses may be beneficial [67].…”
Section: Melatonin As Cancer Prevention and Minimizing Circadian Rhyt...mentioning
confidence: 99%